Shopping centres beyond purchasing of luxury goods - Brochado, Ana (2018)
Brochado, A., Oliveira, C., Rita, P., & Oliveira, F. (2018). Shopping centres beyond purchasing of luxury goods: a tourism perspective. Annals of Leisure Research. DOI: 10.1080/11745398.2018.1522594